Fostering tacit knowledge sharing and innovative work behaviour: an integrated theoretical view. (4th December 2019) - Gupta, Vikas; Thomas, Asha
A pivotal role is played by innovative work behaviour (IWB) for the lasting existence of knowledge-intensive business organisations. Although it is significant to be innovative and creative, the influences of this innovation and creativity on the economy and its growth in the future are still inadequate. This conceptual research, supported by the social capital theory (SCT) and self-determination theory (SDT), attempts to focus on vital predictors that are important for promoting tacit knowledge sharing (KS). This study also concentrates on IWB as an outcome of tacit KS as it enhances the idea of contributing to the existing literature not explored earlier by other related studies.